What is relevant in a text document a machine learning based approach - Mahmud, Abdullah Al; Noor, Jannat-E; Reshad, Sadman Alam; Fuad, Syed Nafis (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.